The Role of Motivation and Teacher Support in Enhancing Elementary Students' Physical Fitness Through Rhythmic Gymnastics Program - Azizah, Maulida Nur; Jusuf, Jeane Betty Kurnia; Santoso, Januar Abdilah; Intani, Andini Dwi; Prayogo, Giri (Universitas PGRI Palembang, 2025)
This study investigates the influence of student motivation and teacher support on predicting physical fitness levels in primary school pupils engaged in rhythmic gymnastics programs. Employing a correlational quantitative methodology, data were gathered from 53 fourth-grade pupils at SD Al-Firdaus Islamic School in Samarinda during April and May 2025. Three validated surveys assessed student motivation (10 items), teacher support (8 items), and physical fitness (7 items) utilizing a 4-point Likert scale. The results indicated substantial positive connections among motivation and physical fitness (r=0.684, p<0.01), teacher support and physical fitness (r=0.496, p<0.01), as well as motivation and teacher support (r=0.642, p<0.01). Multiple regression analysis indicated that motivation and teacher support collectively accounted for 52.3% of the variance in physical fitness (R²=0.523, F=26.914, p<0.001). Motivation was identified as the more significant predictor (β=0.547, p<0.001) in contrast to teacher support (β=0.145, p=0.284). These findings underscore the vital importance of inner and extrinsic motivation in improving physical fitness via rhythmic gymnastics, while instructor support offers significant contextual facilitation.